2021
DOI: 10.1364/osac.436245
|View full text |Cite
|
Sign up to set email alerts
|

Optical tunnels: long-range optical trapping and manipulation in aqueous media

Abstract: In this study, we demonstrate an asymmetric counter-propagating beam system with engineered optical forces allowing for long-range particle trapping and manipulation. We achieved this by breaking the symmetry of the well-known counter-propagating optical trapping beams. By doing so, we extend the range of optical forces for particle confinement and transportation to significantly larger foci separations, creating an optical tunnel. These tunnels are capable of moving matter forward and back with controllable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In the ACP dual beam trapping system [42], unlike the traditional symmetric CP beams setup, we utilize two different optics with very different focal lengths to create the trap. To this end, a lens with a long focal length of 15cm (hence long Rayleigh range) is placed on one side of the sample, while a low-NA objective (0.25 to 0.4 depending on particle size) is placed on the other side.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the ACP dual beam trapping system [42], unlike the traditional symmetric CP beams setup, we utilize two different optics with very different focal lengths to create the trap. To this end, a lens with a long focal length of 15cm (hence long Rayleigh range) is placed on one side of the sample, while a low-NA objective (0.25 to 0.4 depending on particle size) is placed on the other side.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
“…In this work, to generate the ACP trap, we use a more simpli ed system compared to our previous work [42] that uses only one incoming laser beam, as observed in Fig. 1.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, we addressed the first question by utilizing dual Asymmetrical Counter-Propagating (ACP) beams along with the use of low-NA components to form the optical trap 44 , 45 . We showed that the asymmetry introduced in the two CP beam system not only increases trapping stiffness (with respect to traditional CP beam traps) but also allows for the axial scattering forces to be balanced over a wide spatial length.…”
Section: Introductionmentioning
confidence: 99%